2020
DOI: 10.1088/2399-6528/abb218
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of coupled 1D non-linear Burgers’ equation by using Homotopy Perturbation Method (HPM): A review

Abstract: In the current paper, a review of the Homotopy perturbation method is offered thoroughly to fetch the analytical solution of coupled 1D non-linear Burgers’ equation. The exact solution of the coupled 1D Burgers’ equation is attained in the system of a power series, (convergent in nature). A suitable optimal of the initial condition leads towards the vital exact solution after some iterative phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the contrary, the system of the peripheral region cannot be solved exactly, so we adopted the scheme of perturbation (HPM) [46][47][48] in which the same linear operator is chosen for velocity, heat, and energy functions, i.e., H � z 2 /zr 2 + 1/rz/zr. After using the routine calculation of HPM, the final solutions have been composed in subsequent forms:…”
Section: Solution Methodsmentioning
confidence: 99%
“…On the contrary, the system of the peripheral region cannot be solved exactly, so we adopted the scheme of perturbation (HPM) [46][47][48] in which the same linear operator is chosen for velocity, heat, and energy functions, i.e., H � z 2 /zr 2 + 1/rz/zr. After using the routine calculation of HPM, the final solutions have been composed in subsequent forms:…”
Section: Solution Methodsmentioning
confidence: 99%
“…Several integral transforms are developed, such as: the Sumudu transform, Elzaki transform, Natural transform, Pourreza transform, G-transform, Sawi transform, Shehu transform, and others [1][2][3][4][5][6][7][8][9]. These transforms provided in the literature are applied to solve several integral equations, ODEs, PDEs, and fractional PDEs [10][11][12][13][14][15][16][17]. Fusion of these transforms with semi-analytical techniques such as ADM, DTM, HPM, and VIM can also create novel and efficient regimes to solve such equations [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they concluded that numeri-cal experiments demonstrate that the present method has potential for real engineering problems. Kapoor 24 has offered a review of the Homotopy perturbation method to fetch the analytical solution of coupled 1D non-linear Burgers equation. The author has attained the exact solution of the coupled 1D Burgers equation in the system of a power series (convergent in nature).…”
Section: Introductionmentioning
confidence: 99%